China’s carbon dioxide emission forecast based on improved marine predator algorithm and multi-kernel support vector regression - Qin, Xiwen; Zhang, Siqi; Dong, Xiaogang; Zhan, Yichang; Wang, Rui; Xu, Dingxin (Environmental science and pollution research international, 2023)
Global warming has constituted a major global problem. Carbon dioxide emissions from the burning of fossil fuels are the main cause of global warming. Therefore, carbon dioxide emission forecasting has attracted widespread attention. Aiming at the problem of carbon dioxide emissions forecasting, this paper proposes a new hybrid forecasting model of carbon dioxide emissions, which combines the marine predator algorithm (MPA) and multi-kernel support vector regression. For further strengthening the prediction accuracy, a novel variant of MPA is proposed, called EGMPA, which introduces the elite opposition-based learning strategy and the golden sine algorithm into MPA. Algorithm test results show that EGMPA can effectively improve the convergence speed and optimization accuracy. The carbon dioxide emission data of China from 1965 to 2020 are taken as the research objects. Root-mean-square error (RMSE), mean absolute error (MAE), and mean absolute percentage error (MAPE) are used to evaluate the performance of the proposed model. The proposed multi-kernel support vector regression model is used to forecast China’s carbon dioxide emissions during the “14th Five-Year Plan” period. The results show that the proposed model has RMSE of 37.43 Mt, MAE of 30.63 Mt, and MAPE of 0.32%, which significantly improves the prediction accuracy and can accurately and effectively predict China’s carbon dioxide emissions. During the “14th Five-Year Plan” period, China’s carbon dioxide emissions will continue to show an increasing trend, but the growth rate will slow down significantly.